Temperature Impact on Lithium Metal Morphology in Lithium Reservoir-Free Solid-State Batteries - Min-Gi Jeong; Kelsey B. Hatzell; Sourim Banerjee; Bairav S. Vishnugopi; Partha P. Mukherjee (PRX Energy)
Lithium reservoir-free solid-state batteries can offer exceedingly high energy densities for a range of emerging applications related to aviation and electric vehicles. However, reversible operation of reservoir-free cells is plagued by a range of degradation mechanisms. The morphology of lithium metal film and subsequent evolution during operation can be highly variable and is dependent on the type of solid electrolyte, current collector, and operating conditions (current density, temperature, pressure, etc.). Here we evaluate lithium metal vertical and horizontal growth mechanisms at an argyrodite solid electrolyte–stainless steel interface at various temperatures from 25 to 80^{∘}C. Combining confocal imaging and mesoscale modeling, we demonstrate how lithium metal island agglomeration is accelerated at elevated temperatures and facilitates greater horizontal growth of lithium metal. Maintaining high active material contact (e.g., horizontal growth) is critical for the formation of reversible lithium metal anodes in reservoir-free cells.